OPTIMALISASI PENERAPAN PENDEKATAN KONTEKSTUAL BERBASIS PEMBELAJARAN SOSIAL UNTUK MENINGKATKAN HASIL BELAJAR IPAS MATERI GERAK BENDA PADA SISWA KELAS III SD NEGERI 03 SIKASUR - Dhiemas; Ryan Dwi Puspita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
IPAS learning in elementary schools not only emphasizes factual mastery but also conceptual understanding related to students' social lives and real experiences. However, third-grade students still experience difficulties in understanding the concept of object motion. This study aims to optimize the application of a social learning-based contextual approach to improve IPAS learning outcomes on the topic of object motion for third-grade students at SD Negeri 03 Sikasur. This study used Classroom Action Research (CAR) conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. The subjects were 36 third-grade students. The results showed a significant improvement in student learning outcomes. In Cycle I, the percentage of students achieving mastery reached 67.22%, which then increased in Cycle II to 83.33%. In addition, student activeness and cooperation also improved. Thus, the contextual approach based on social learning is effective in improving IPAS learning outcomes on the topic of object motion.